Advanced environmental monitoring with remote sensing time series data and R - Gemitzi, Alexandra; Koutsias, Nikolaos; Lakshmi, Venkataraman, 1966- (CRC focus series., 2020)
"This book provides a step-by-step guide on how to use various publicly available remotely sensed time series data sources for environmental monitoring and assessment. Readers will learn how to extract valuable information on global changes from a 20-year collection of ready-to-use remotely sensed data through the free open statistical software R and its geographic data analysis and modeling tools. The case studies are from the Mediterranean region--a designated hot spot regarding climate change effects. Each chapter is dedicated to specific remote sensing products chosen for their spatial resolution. The methods used are adapted from large-scale to smaller-scale problems for different land cover areas."--Provided by publisher